2015
DOI: 10.1038/srep09320
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Fe3O4 Particles with Novel Nanosheets Morphology and Magnetochromatic Property by a Modified Solvothermal Method

Abstract: Novel-morphological Fe3O4 nanosheets with magnetochromatic property have been prepared by a modified solvothermal method. Such nanosheets could form one-dimension photonic crystal under an external magnetic field. The Fe3O4 nanosheets suspension could strongly diffract visible light and display varied colors with changing the intensity of the magnetic field. The photonic response is rapid, fully reversible and widely tunable in the entire visible spectrum. Excellent magnetic properties of these Fe3O4 nanosheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(64 citation statements)
references
References 22 publications
(20 reference statements)
5
58
0
1
Order By: Relevance
“…A simple strategy was developed by Wang et al [98], which consists of microwave-assisted coprecipitation of ferrous sulphate in a mixture of ethylene glycol and water, affording nanosheets with good crystallinity and saturation magnetization around 30 emu/g. Zhuang et al [99] were able to synthesize magnetite nanosheets through a solvothermal method using diethylene glycol, which, through the inhibition of the crystal plane (111), favours the formation of magnetite sheet-like crystals. Furthermore, the authors demonstrated that the nanoparticles self-assemble into chain-like structures along the direction of the external magnetic field, known as photonic crystals, which display a magnetochromatic property.…”
Section: Nano-films Sheets and Platesmentioning
confidence: 99%
“…A simple strategy was developed by Wang et al [98], which consists of microwave-assisted coprecipitation of ferrous sulphate in a mixture of ethylene glycol and water, affording nanosheets with good crystallinity and saturation magnetization around 30 emu/g. Zhuang et al [99] were able to synthesize magnetite nanosheets through a solvothermal method using diethylene glycol, which, through the inhibition of the crystal plane (111), favours the formation of magnetite sheet-like crystals. Furthermore, the authors demonstrated that the nanoparticles self-assemble into chain-like structures along the direction of the external magnetic field, known as photonic crystals, which display a magnetochromatic property.…”
Section: Nano-films Sheets and Platesmentioning
confidence: 99%
“…Such nanosheets could form one-dimension photonic crystal under an external magnetic field. The Fe3O4 nanosheets suspension could strongly diffract visible light and display varied colors with changing the intensity of the magnetic field [34]. Monodisperse superparamagnetic MNPs coated with oleic acid have been prepared by thermal decomposition of Fe(III) glucuronate.…”
Section: Thermal Decomposition and Combustionmentioning
confidence: 99%
“…Secondly, the FNPs were modified with PAA as follow. PAA was synthesized by the method which has been described in detail in another paper 36 . 20 mL NaOH solution (1.0 mmol/L) was added into the wet Fe 3 O 4 precipitation in a beaker, and then the mixture was ultrasonically treated to form FNPs suspension.…”
Section: Methodsmentioning
confidence: 99%